Allergic Rhinitis Improvement in Asthmatic Children After Using Acaricidal Bait: A Randomized, Double-Blind, Cross-Placebo Study - Chen, Ming; Wu, Yufen; Yuan, Shuhua; Tang, Mingyu; Zhang, Lei; Chen, Jiande; Li, Luanluan; Wu, Jinhong; Zhang, Jing; Yin, Yong (Frontiers in Pediatrics, 2021)
Objective: This study aimed to evaluate the effects of acaricidal bait use on the house dust mite (HDM) allergen concentration and occurrence of allergic rhinitis (AR) and asthma symptoms in children sensitized to HDMs. Study Design: Sixty-six children (3–12 years old) with AR and asthma sensitized to HDMs were randomly assigned to receive an acaricidal bait intervention for 8 weeks and a placebo intervention for 8 weeks separated by a 4-week washout period. The visual analog scale (VAS) score, rhinitis control assessment test (RCAT) score, rhinoconjunctivitis quality of life questionnaire (RQLQ) score, asthma control questionnaire-5 (ACQ-5) score and HDM allergen levels were monitored. Results: HDM allergen levels were significantly decreased after 8 weeks (Δder p2+f2 2.282 (3.516) μg/g vs. 0.147 (0.25) μg/g, P < 0.05) in the acaricidal bait group compared with the placebo group. The VAS, RCAT and RQLQ scores in the acaricidal bait group were also significantly improved (ΔVAS 7.5 (16) vs. 3 (18), P < 0.05; ΔRCAT−3 (5) vs. 0 (7), P < 0.05; ΔRQLQ 4.5 (8) vs. 1 (8), P < 0.05), but the ACQ-5 score did not improve (ΔACQ-5 0.2 (0.4) vs. 0 (0.65), P > 0.05). Conclusion: Acaricidal bait reduced HDM exposure and improved rhinitis symptoms. This trial is registered at www.chictr.org.cn.